Bet On It. - Cherry, S. (IEEE spectrum)
ArcelorMittal, Best Buy, General Electric, Hewlett-Packard, Nokia, and Samsung have all begun tapping into the "wisdom of crowds" to help them predict public reaction to new products, the future price of a commodity, or sales revenue in the next quarter. In the past few years, the technique has really taken off, with at least a dozen start-ups competing for business in the field. Some offer software and services to help companies tap the wisdom of their workers or the outside world. Others create markets that allow anyone to go to a Web site to bet or even to pose a question that can be bet on. It's not surprising that Internet-based mechanisms can be found to tap into the wisdom of the masses. What's surprising is that there's a way to draw it out so quickly and efficiently. And that it works so well.